THE IMPACT OF GREEN BANKING ON THE FINANCIAL PERFORMANCE OF BANKS IN MALAYSIA. - Piere Philicha, Johen; Nazaria, Md. Aris; Razman, Anuar; Muhammad Syakir Khusyairi, Mohd Yatim (UNIMAS Publisher, 2025)
This study aims to investigate how green banking impacts the financial performance of Malaysian commercial banks. To accomplish this, the research used theories like Natural Resource-Based View, Innovation Theory, and Stakeholder Theory. By analysing secondary data from 15 banks over six years (2018-2023). While prior research by Sharif, Sofuoglu, Kocak, and Anwar (2024) identified a knowledge gap in green banking within Malaysia, this study seeks to bridge that gap. The results indicate that green finance initiatives may positively influence the financial performance of banks. This study offers valuable perspectives for policymakers, regulators, and financial institutions by underscoring the importance of promoting green finance initiatives. By exploring the link between green finance and financial outcomes, banks are equipped to make informed choices that bolster their sustainability efforts and strengthen their long-term financial health. It encourages banks to embed sustainability within their business strategies, enabling them to not only support environmental sustainability but also enhance their financial performance, fostering a resilient and sustainable future. Keywords: Operational efficiency, loan-to-deposit ratio, non-performing loan, return on assets.INTRODUCTIONThis study investigates the impact of green banking on the financial performance of banks in Malaysia. Green banking involves the integration of environmental sustainability into the operations and services of financial institutions. As global awareness ofenvironmental issues increases, many banks are adopting green banking practices to contribute to sustainable development, reduce their carbon footprint, and offer environmentally-friendly financial products. The primary focus of this research is to assesshow these green banking initiatives influence the financial performance of banks in Malaysia, considering key financial indicators such as profitability, cost efficiency, and overall market competitiveness. This chapter introduces the research topic and provides a framework for the study. It begins by outlining the background of the study, which presents the context and relevance of the research. It then defines the problem statement, explaining the need for this study and highlighting the gap in current literature. The research questions and research objectives are also clearly stated, guiding the direction of the study. In addition, this chapter emphasizes the significance of the study, highlighting its potential contributions to the banking sector and policy development. Finally, the scope of the study is defined, and an overview of the organization of the thesis is provided, summarizing the structure and contents of the following chapters.This study is motivated by the increasing global and national emphasis on sustainable finance. In Malaysia, green banking remains an emerging area with limited empirical evidence on how